Evaluation of reported sediment samples from 20 Ma using a molecular phylogenetic approach: comment on Liu et al. (2017). (4th February 2020) - Segawa, Takahiro; Yonezawa, Takahiro
Summary: Liu et al. reported the cultivation and DNA sequencing of 69 fungal isolates (Ascomycota and Basidiomycota) from ancient subseafloor sediments, suggesting that they represent living fungal populations that have persisted for over 20 million years. Because these findings could bring about a paradigm shift in our understanding of the spatial breadth of the deep subsurface biosphere as well as the longevity of ancient DNA, it is extremely important to verify that their samples represent pure ancient fungi from 20 million years ago without contamination by modern species. For this purpose, we estimated the divergence times of Dikarya (Ascomycota + Basidiomycota) and Mucoromycota fungi assuming that the fungal isolates were actually sampled from 20 Ma (mega‐annum) sediments and evaluated the validity of the sample ages. Using this approach, we estimate that the age of the last common ancestor of Dikarya and Mucoromycota fungi greatly exceeds the age of the Earth. Our finding emphasizes the importance of using reliable approaches to confirm the dating of ancient samples.